Studtite dissolution in the presence of organic complexants relevant to nuclear waste disposal - Zachary Murphy; Rachel Cohen; David Rai II; Cassandra Munoz; Caleb Johnson; Edwin Davidson; Swadeshmukul Santra; Vasileios Anagnostopoulos (Hydrometallurgy, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Beyond genes and environment: mapping biological stochasticity in aging - Adam J. Hruby; Gilberto Garcia; Max A. Thorwald; Caleb E. Finch; Joshua Johnson; Ryo Higuchi-Sanabria (GeroScience, 2025)
Aging is characterized by extensive variability in the onset of morbidity and mortality, even in genetically identical populations with carefully controlled environments. This points to the important role stochasticity plays in shaping the divergent aging process between individual organisms. Here, we survey how stochastic factors at the level of molecules, cells, tissues, and organisms manifest in and impact the aging process, with a focus on the nematode Caenorhabditis elegans . Findings of stochasticity in C. elegans give additional insights for aspects of aging in the more complex settings of mammals with parallels drawn between organisms when appropriate. The emerging understanding of the stochastic contributors to longevity will enhance research strategies and medical interventions for personalized medicine.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Recovery of an Acid Mine Drainage-Impacted Stream Treated by Steel Slag Leach Beds - Natalie Kruse; Caleb Hawkins; Dina L. López; Kelly Johnson (Mine Water and the Environment, 2019)

The perpetual state of emergency that sacrifices protected areas in a changing climate - Dirac Twidwell; Carissa L. Wonkka; Christine H. Bielski; Craig R. Allen; David G. Angeler; Jacob Drozda; Ahjond S. Garmestani; Julia Johnson; Larkin A. Powell; Caleb P. Roberts (Conservation Biology, 2018)
A modern challenge for conservation biology is to assess the consequences of policies that adhere to assumptions of stationarity (e.g., historic norms) in an era of global environmental change. Such policies may result in unexpected and surprising levels of mitigation given future climate‐change trajectories, especially as agriculture looks to protected areas to buffer against production losses during periods of environmental extremes. We assessed the potential impact of climate‐change scenarios on the rates at which grasslands enrolled in the Conservation Reserve Program (CRP) are authorized for emergency harvesting (i.e., biomass removal) for agricultural use, which can occur when precipitation for the previous 4 months is below 40% of the normal or historical mean precipitation for that 4‐month period. We developed and analyzed scenarios under the condition that policy will continue to operate under assumptions of stationarity, thereby authorizing emergency biomass harvesting solely as a function of precipitation departure from historic norms. Model projections showed the historical likelihood of authorizing emergency biomass harvesting in any given year in the northern Great Plains was 33.28% based on long‐term weather records. Emergency biomass harvesting became the norm (>50% of years) in the scenario that reflected continued increases in emissions and a decrease in growing‐season precipitation, and areas in the Great Plains with higher historical mean annual rainfall were disproportionately affected and were subject to a greater increase in emergency biomass removal. Emergency biomass harvesting decreased only in the scenario with rapid reductions in emissions. Our scenario‐impact analysis indicated that biomass from lands enrolled in the CRP would be used primarily as a buffer for agriculture in an era of climatic change unless policy guidelines are adapted or climate‐change projections significantly depart from the current consensus.

Evidence for male alternative reproductive tactics in convict cichlids (Amatitlania siquia) in Lake Xiloá, Nicaragua - Ethan D. Clotfelter; Elizabeth M. Johnson; Caleb Anderson; Ryan L. Earley (Environmental Biology of Fishes, 2017)